Biological activity of naphthoquinones: Cytotoxic activity against eukaryotic plant cells and against eukaryotic human cells. Antimicrobial activity of naphthoquinones against selected microorganisms - Pedrosa, Inês Duarte Ferreira (2018)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2017